On rational functions of the best nonsymmetric approximations in integral metrics - Polyakov, O. V.; Ruchaevskaya, N. O. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain theorems that characterize the degree of the rational function of the best $(α, β)$ -approximation in the space $L_p$ and conditions under which the value of the best rational $(α, β)$ -approximation is less than the best $(α, β)$ -approximation byalgebraic polynomials.